FORECASTING MONTHLY RAINFALL BY GOMPERTZ CURVE TECHNIQUE - Tomar, A.S.; Ranade, D.H.; Paradkar, V.K.; Jain, L.K.; Vishwakarma, S.K. (Journal of Soil and Water Conservation, 2022)
The present study was undertaken to develop some deterministic empirical equations to forecast the cumulative monthly rainfall. The results so obtained for the Chhindwara region of Madhya Pradesh clearly show that the gompertz curve technique can be utilized to forecast the monthly rainfall with reasonable accuracy. The methodology can be adopted to forecast the cumulative rainfall at other please too.